A Prospective Analysis of Hyponatremia in Transurethral Resection of Prostate - Aftab Ahmed, Sajid Rehman, Shahjehan, Tauheed Farid, Farooq Malik, Athar Mahmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Transurethral resection of prostate (TURP) is one of the most common urological procedures performed. Objectives: The main objective of the study is to find the hyponatremia in transurethral resection of prostate. Materials and Method: This prospective study was conducted in Shaikh Khaleefa Bin Zaid Hospital/CMH Muzaffarabad AJK, Ganga Ram Hospital Lahore and PKLI Lahore, from May 2020 to April 2021. 60 male patients aged 45 – 75 years presented for TURP were enrolled in the study with ASA classification of grade I and IV. Informed and written consent was obtained from all study subjects. Results: The mean of all study subjects was reported to be 71.58 ± 7.76years. The majority of the patients had grade I or III. Spinal anesthesia was given to 31 patients (62%) and 19 (38%) patients were subjected to general anesthesia. The mean duration of procedure was 72.42 ± 24.77min. The mean size of the resected prostate was 54.82 ± 25.04g with the minimum and maximum size being 21.4 g and 131 g. Blood transfusion was done in only 5 patients (10%). Conclusion: It is concluded that hyponatremia is a common finding in patients undergoing TURP. We observed that duration of operation is one of the deciding factor to determine the level of hyponatremia.